Owner-level taxes and business activity - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2015)
In some classes of models, taxes at the owner level are "neutral" and have no effect on firm activity. However, this tax neutrality is sensitive to assumptions and no longer holds in more complex models. We review recent research that incorporates greater complexity in studying the link between taxes and business activity - particularly entrepreneurship. Dividend taxes on owners of large firms affect firm activity in models that include agency conflicts between owners and managers. Similarly, after incorporating entrepreneurs' occupational choice into the model, taxes are no longer neutral. By forsaking lucrative alternative careers, skilled entrepreneurs tend to have high opportunity costs, which make the choice of attempting to start a business of first order importance. Moreover, in models where it is assumed that capital flows across borders without cost, taxes on domestic business owners do not alter business activity because foreign capital seamlessly compensates for tax-induced declines in investments. This theoretical notion is contradicted by the strong "home bias" observed in business ownership, in particular for small firms and startups without easy access to international capital markets. Recent empirical work has emphasized that taxes have heterogeneous effects on mature firms, entrepreneurial startups, and owner-managed small firms. Lowering dividend taxes on firms with dispersed ownership has been shown to shift capital from mature firms into rapidly growing firms. Moreover, capital gains taxation tends to reduce the number of innovative startups and diminish venture capital activity, while high owner-level taxes encourage small business activity and non-entrepreneurial self-employment because such firms have more opportunities to avoid or evade taxes. To obtain efficient incentives in entrepreneurial startups, contractual terms are required that ex ante guarantee that all providers of critical inputs, especially equity constrained entrepreneurs, are entitled to a share of the resulting capital value firm. Unless properly designed, owner-level taxes prevent such ex ante contracting and thus lower the likelihood of eventual success.
Keywords: L26; H25; H32; H26; 330; Business taxation; Capital income taxation; Corporate governance; Entrepreneurship; Institutions; Tax policy